New biotechnological applications for Ashbya gossypii: Challenges and perspectives. Issue 4 (4th July 2017) - Aguiar, Tatiana Q.; Silva, Rui; Domingues, Lucília
ABSTRACT: The filamentous fungus Ashbya gossypii has long been considered a paradigm of the White Biotechnology in what concerns riboflavin production. Its industrial relevance led to the development of a significant molecular and in silico modeling toolbox for its manipulation. This, together with the increasing knowledge of its genome and metabolism has helped designing effective metabolic engineering strategies for optimizing riboflavin production, but also for developing new A. gossypii strains for novel biotechnological applications, such as production of recombinant proteins, single cell oils (SCOs), and flavour compounds. With the recent availability of its genome-scale metabolic model, the exploration of the full biotechnological potential of A. gossypii is now in the spotlight. Here, we will discuss some of the challenges that these emerging A. gossypii applications still need to overcome to become economically attractive and will present future perspectives for these and other possible biotechnological applications for A. gossypii .